The Role-playing Self: Virtual Ethnography Study of K-Pop Fans’ Idol-roleplaying and Self-identity in Twitter - Mashita Phitaloka Fandia Purwaningtyas; Tabina Azalia Oktara (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
The phenomenon of K-pop idol-roleplaying is on the rise in social media platform, particularly Twitter, among Indonesian youth. Idol-roleplaying refers to the activity where users or role-players create an account under the name and using the identity of their favorite idol, and then using it to interact with other role-players or other fans based on the image and plot that the role-player has determined. This phenomenon evokes question in regards to the identity performed by users or role-players under the veil of their idol’s identity, to the extent of how they interact with fellow role-players using that particular roleplay account. Hence, this research is significant in studying the idol-roleplaying phenomenon and the self-identity performance of fans, particularly in the context of Indonesian youth’s culture. This research is conducted with virtual ethnography method, involving eight role-players as informants. Initial findings highlight the performativity and identity play perform by role-players.